Penggunaan Media Realia dalam Meningkatkan Pengalaman Belajar Siswa - Taqwa Nur Ibad; Maisyatus Sarifah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
Education is an effort to foster and spread one's personality, both spiritually and physically. Learning experiences are several student activities carried out to obtain new information and competencies in accordance with the objectives to be achieved. Realia media are tangible objects that are often encountered by students and are easily found in daily activities that can be brought into learning situations or become media for teaching materials for students. These real objects can be used as realia media and these objects must be original and intact in form and also the actual size so that they can be recognized by students properly. Based on the above understanding, it is known that the use of the right realia media will improve the student's learning experience of the material to be studied. The use of realia media in thematic learning, especially in grade 4 MI Nurul Islam Sukosari. And the problem I encountered was that the media used by grade 4 teachers had not yet optimized the long-term learning objectives. This happens because the use of media is monotonous so that the process of learning activities is less memorable for students so that students are less experienced. Therefore, to improve the student learning experience, the researcher chose to raise the title